2011
DOI: 10.1016/j.immuni.2011.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Silica Crystals and Aluminum Salts Regulate the Production of Prostaglandin in Macrophages via NALP3 Inflammasome-Independent Mechanisms

Abstract: Particulates such as silica crystal (silica) and aluminum salts (alum) activate the inflammasome and induce the secretion of proinflammatory cytokines in macrophages. These particulates also induce the production of immunoglobulin E via a T helper 2 (Th2) cell-associated mechanism. However, the mechanism involved in the induction of type 2 immunity has not been elucidated. Here, we showed that silica and alum induced lipopolysaccharide-primed macrophages to produce the lipid mediator prostaglandin E₂ (PGE₂) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(155 citation statements)
references
References 58 publications
10
140
1
4
Order By: Relevance
“…Either NADPH oxidase or cyclooxygenase-2 (COX-2) is believed to contribute to ROS production in response to NLRP3-mediated inflammation. 15,16 The expression levels of p47phox, a subunit of NADPH oxidase and of COX-2 were analyzed by western blotting techniques. The levels of cytosolic p47phox and COX-2 proteins were increased in response to MSU in a dosedependent manner (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Either NADPH oxidase or cyclooxygenase-2 (COX-2) is believed to contribute to ROS production in response to NLRP3-mediated inflammation. 15,16 The expression levels of p47phox, a subunit of NADPH oxidase and of COX-2 were analyzed by western blotting techniques. The levels of cytosolic p47phox and COX-2 proteins were increased in response to MSU in a dosedependent manner (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to mention that other mediators and cell types not analyzed in the present study could contribute to MSU crystal-induced hypernociception. For example, a recent study demonstrated that particulate materials, including silica crystals and aluminum salt, are able to induce prostaglandin E 2 production independent of the NLRP3 inflammasome (40).…”
Section: Discussionmentioning
confidence: 99%
“…Potassium deficiency in plants usually induces brown scorching and curling of leaf tips as well as chlorosis (yellowing) between leaf veins, which accelerate leaf senescence. Leaf photosynthesis consists of the several physiological processes, including light harvesting, photosystem II (PSII) photochemistry and CO2 assimilation [7]. Chlorophyll fluorescence measurements have increasingly been used as a non-invasive tool in leaf ecophysiological studies.…”
Section: Introductionmentioning
confidence: 99%